Characterization of silicon nanocrystals embedded in SiO2 matrix - Liu, Yang (2008)
In this thesis, we have synthesized Si nanocrystals (nc-Si) embedded in SiO2 films by implanting Si+ into SiO2 films that are thermally grown on Si substrates.